The impact of the COVID-19 pandemic on elective laparoscopic cholecystectomy: A retrospective Cohort study - Demetriou, George; Wanigasooriya, Kasun; Elmaradny, Ahmed; Al-Najjar, Ammar; Rauf, Mohammad; Martin-Jones, Alicia; Aboul-Enein, Mohamed Saad; Robinson, Steven J; Perry, Anthony; Wadley, Martin S; Mourad, Moustafa (Frontiers in Surgery, 2022)
The coronavirus disease 2019 (COVID-19) pandemic had a significant impact on elective surgery for benign disease. We examined the effects of COVID-19 related delays on the outcomes of patients undergoing elective laparoscopic cholecystectomy (LC) in an upper gastrointestinal surgery unit in the UK. We have analysed data retrospectively of patients undergoing elective LC between 01/03/2019 to 01/05/2019 and 01/04/2021 to 11/06/2021. Demographics, waiting time to surgery, intra-operative details and outcome data were compared between the two cohorts. Indications for surgery were grouped as inflammatory (acute cholecystitis, gallstone pancreatitis, CBD stone with cholangitis) or non-inflammatory (biliary colic, gallbladder polyps, CBD stone without cholangitis). A p value of <0.05 was used for statistical significance. Out of the 159 patients included, 106 were operated pre-pandemic and 53 during the pandemic recovery phase. Both groups had similar age, gender, ASA-grades and BMI. In the pre-pandemic group, 68 (64.2%) were operated for a non-inflammatory pathology compared to 19 (35.8%) from the recovery phase cohort (p < 0.001). The waiting time to surgery was significantly higher amongst patients operated during the recovery phase (p = 0000.1). Less patients had complete cholecystectomy during the pandemic recovery phase (p = 0.04). There were no differences in intraoperative times and patient outcomes. These results demonstrate the impact of COVID-19 related delays to our cohort, however due to the retrospective nature of this study, the current results need to be backed up by higher evidence in order for strong recommendations to be made.